Imine formation as a simple reaction to construct copper-reactive cruciform fluorophores - Schwaebel, S. Thimon; Schäfer, Vera; Wenz, Jan; Coombs, Benjamin A.; Tolosa, Juan; Bunz, Uwe H. F. (The journal of organic chemistry, 2013)
We developed a series of new conjugated cruciform fluorophores (XF) featuring imine groups. The condensation of an XF containing aldehyde functionalities and selected primary amines leads to several XF-imine derivatives. Upon addition of Cu2+ or Zn2+ ions to solutions of the imine XFs in different solvents, a red-shifted emission is detected, resulting in an altered emission color. The imine acts as a simple modular metallo-reactive fluorophore.
Published: November 29, 2012
Gesehen am 02.08.2021